A statistical viewpoint on the use of GPS information in wireless ad hoc protocols. (7th September 2007) - Guardiola, Ivan G.; Matis, Timothy I.
In this paper, we consider the impact of fast fading effects on the discovery and maintenance of routes in a MANET. We provide a statistical interpretation of link quality-based on the instantaneous received power under a mulitpath fading model, for which associated types one and two errors are defined. Based on this viewpoint, we propose embedding GPS information into the AODVjr protocol to block the discovery of routes with unreliable links and thereby enhance end-to-end performance of the system.